Peculiar features of men physical condition in planning highly intensive physical loads in winter period - O.B. Pryshva (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Physical functioning of average and high intensity is an important component of mature men's health and longevity. For highly intensive physical functioning organism's physical fitness is required. Human physical condition can change under influence of season factors. Purpose: to determine specific features of men's physical condition before their highly intensive physical trainings in winter period and test them. Material: 25 men of 35-48 years' age without chronic diseases were chosen for experiment. All they observe healthy life style. Body mass index, physical condition by methodic of Bayevskie were tested. The research was conducted in the following way: in the morning and in the evening of every day. Physical functioning was tested by methodic IPAQ. Results: we registered confident (p-0.05) distinctions in men's physical condition before and in the day of their highly intensive physical functioning. We noticed changes in the following: body weight, heart beats rate, adaptation potential of Bayevskiy. The most significant indicator was the marker. For testing of its effectiveness we offered for men to plan highly intensive physical functioning in compliance with this marker during one month. Result was confident (p-0.05) increase of duration and quantity of highly intensive physical trainings, improvement of physical condition by 3.13% in complex test of Bayevskiy. Conclusions: Consideration of men's physical condition plays important role in planning their highly intensive physical functioning. Increment of Bayevskiy's adaptation potential by 5.25% can be informative marker in winter period. It is a factor for highly intensive physical functioning planning for definite day.